Rapid recovery from near-fatal immune reconstitution inflammatory syndrome and acute respiratory distress syndrome following neutropenic recovery by cytokine adsorption - Karl Bihlmaier; Laura Vonbrunn; Axel Schmid; Larissa Herbst; Krystyna Bujok; Felix A. Büstgens; Rebecca Wätzig; Heidi Waibel; Mario Schiffer; Carsten Willam (BMC Pulmonary Medicine, 2026)
Abstract Background In the presence of clinical or microbiological evidence of pneumonia, emerging leukocytes in recovery from neutropenia undergo substantial migration to the site of infection, where they elicit immunogenic reactions. The administration of granulocyte colony-stimulating factors is a risk factor for dysregulation of this immune response, which can lead to ARDS. However, there is a paucity of knowledge regarding the severe forms of near-fatal IRIS. Case presentation This case report describes the successful treatment of a hematologic patient with life-threatening Immune Reconstitution Inflammatory Syndrome after recovery from neutropenia and a subsequent acute respiratory distress syndrome involving cytokine adsorption. The present report delineates the case of a 65-year-old male afflicted with plasmoblastic lymphoma and neutropenic sepsis with pneumonia. Escherichia coli was identified in bronchoalveolar lavage fluids, and the patient was successfully treated with piperacillin and tazobactam. After recovering from neutropenia, the patient's respiratory function abruptly worsened, resulting in a secondary, severe ARDS. This deterioration was accompanied by increasing interleukin-6 levels. Therapeutic approaches as prone positioning or volume depletion using renal replacement therapy with high ultrafiltration rates did not lead to a significant respiratory improvement. Initiation of cytokine adsorption resulted in an immediate and absolute respiratory recovery. Conclusions Immune reconstitution inflammatory syndrome might cause dysregulated pulmonary immune responses following recovery from neutropenia with consecutive severe ARDS. This case report is the first to link IRIS-induced severe ARDS to a hyperinflammatory condition and to the successful therapeutic approach of cytokine adsorption. Ultimately, only cytokine adsorption was able to rapidly improve this suspected IRIS-associated hyperinflammation in an otherwise life-threatening ARDS.